Sejarah dan Perkembangan Yayasan Umat Islam Kaliyoso (YAUMIKA) serta Kontribusinya Bagi Masyarakat Kecamatan Kalijambe Kabupaten Sragen Tahun 1969-2015 - Ida Ayu Cahyani; Martina Safitry; Latif Kusairi (Keraton: Journal of History Education and Culture, 2022)
This study is a historical study of the development of local Islam in Kaliyoso Village, Kalijambe District, Sragen Regency, Central Java. Kaliyoso was the forerunner of the spread of Islam in the northern region of Surakarta City. The teachings of Islam in Kaliyoso were first spread by a cleric descended from a local Muslim family named Kiai Abdul Jalal I (Bagus Turmudi). After paying attention to the steps of the struggle of Kiai Abdul Jalal I in developing the Islamic religion, the struggle for preaching from Kiai Abdul Jalal I was continued by the sons of Wayah Kaliyoso with an effort to establish a foundation called the Yayasan Umat Islam Kaliyoso (YAUMIKA) in 1969. This research using a historical methodology that has four main stages of historical methods, namely (1) heuristics, (2) verification, (3) interpretation, (4) historiography. The results of this study indicate that the Yayasan Umat Islam Kaliyoso (YAUMIKA) has a role and contribution in efforts to foster the Kaliyoso community towards a more advanced civilization, as well as organize Islamic community activities. This was done with the aim of spreading the religion of Islam and the welfare of the people of Kaliyoso and its surroundings.